2008
DOI: 10.1080/10408390701425615
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Proteins and Peptides

Abstract: Proteins can inhibit lipid oxidation by biologically designed mechanisms (e.g. antioxidant enzymes and iron-binding proteins) or by nonspecific mechanisms. Both of these types of antioxidative proteins contribute to the endogenous antioxidant capacity of foods. Proteins also have excellent potential as antioxidant additives in foods because they can inhibit lipid oxidation through multiple pathways including inactivation of reactive oxygen species, scavenging free radicals, chelation of prooxidative transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
683
1
27

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,115 publications
(733 citation statements)
references
References 97 publications
22
683
1
27
Order By: Relevance
“…Our results showed no effect of the position of the Trp residue in the dipeptide on XO inhibition, suggesting that the N or C-terminal location of Trp does not affect its bioactivity. Amino acids have been reported to display a lower anti-oxidant activity compared to peptides as they have a lower radical scavenging activity [19]. In contrast, we found that Trp displayed a similar XO IC 50 inhibition has yet to be fully determined [79] No XO inhibition was observed with hydrolyzates of complex protein substrates such as WPI, WPI Ret and NaCN.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Our results showed no effect of the position of the Trp residue in the dipeptide on XO inhibition, suggesting that the N or C-terminal location of Trp does not affect its bioactivity. Amino acids have been reported to display a lower anti-oxidant activity compared to peptides as they have a lower radical scavenging activity [19]. In contrast, we found that Trp displayed a similar XO IC 50 inhibition has yet to be fully determined [79] No XO inhibition was observed with hydrolyzates of complex protein substrates such as WPI, WPI Ret and NaCN.…”
Section: Discussionmentioning
confidence: 54%
“…Certain amino acid structures have been correlated with high antioxidant properties. These include amino acids with sulfur residues (Cys and Met) and aromatic structures (Trp, Tyr, His and Phe) [19,48,60,73,75]. Phenol and indole groups in amino acids can act as potential hydrogen donors [70,73,75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the proliferation of short chain peptides and amino acids generated from protein hydrolysis showed potential effects on inhibition of lipid oxidation via scavenging free radical and reduction of hydroperoxide (Elias et al 2008). …”
Section: Tbarsmentioning
confidence: 99%
“…On the other hand oxidative reactions in foods lead to the deterioration of quality attributes such as flavor, aroma, texture, and color (Park et al 2001). In lipid peroxidation, these reactions typically involve free radical pathways that result in the formation of lipid hydroperoxides, which are eventually decomposed to low molecular weight carbonyls in the presence of prooxidants (Elias et al 2008). A potent scavenger of these species may serve as a possible preventive intervention for free radical mediated diseases (Gutteridge and Halliwell 2010).…”
Section: Introductionmentioning
confidence: 99%